1977
DOI: 10.1111/j.1745-4565.1977.tb00254.x
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Nitrosamines in Some Traditional Southern Chinese Food Products

Abstract: Previous epidemiological studies of nasopharyngeal carcinoma suggest that traditional food items, particularly salted fish, consumed by southern Chinese may play a role in the cause of the high frequency of the disease among them. We report here the results of an analysis by combined gas chromatography and high resolution mass spectrometry of six types of salted fish and ten other items of traditional southern Chinese salted food products for the presence of volatile nitrosamines. Only N‐nitroso‐dimethylamine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1981
1981
1989
1989

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…We observed the highest level of NDMA in hard, salted, dried fillet of garouper (Epinephelus asciutus) in China; however, the range of NDMA levels in 14 varieties of Chinese salted fish was wide, (0 -14 pglkg) with a mean of 3 pg/kg ( Table I). Similar wide ranges of NDMA levels in Chinese fish samples have been reported by Fong and Chan (1977), Huang et al (1977Huang et al ( , 1978aHuang et al ( , 1981 and Tannenbaum et aE. (1985).…”
Section: Discussionsupporting
confidence: 69%
“…We observed the highest level of NDMA in hard, salted, dried fillet of garouper (Epinephelus asciutus) in China; however, the range of NDMA levels in 14 varieties of Chinese salted fish was wide, (0 -14 pglkg) with a mean of 3 pg/kg ( Table I). Similar wide ranges of NDMA levels in Chinese fish samples have been reported by Fong and Chan (1977), Huang et al (1977Huang et al ( , 1978aHuang et al ( , 1981 and Tannenbaum et aE. (1985).…”
Section: Discussionsupporting
confidence: 69%
“…However, their descendants, who became adapted to a new life-style, are at lower risk of NPC (Zippin et al, 1962;King and Haenszel, 1973;Buell, 1974). Several studies Chan, 1973, 1977;Huang et al, 1977Huang et al, , 1978Huang et al, , 1981Tannenbaum et al, 1985;Poirier et al, 1987) have shown that some samples of Cantonese-style salted fish contained relatively high levels of volatile nitrosamines, all of which induce tumors in the nasal cavities of experimental animals (Druckrey et al, 1967;Magee et al, 1976).…”
mentioning
confidence: 99%